Estimating the stopping power distribution during proton therapy: A proof of concept - Ferrero, Veronica; Werner, Julius; Cerello, Piergiorgio; Fiorina, Elisa; Vignati, Anna; Pennazio, Francesco; Rafecas, Magdalena (Frontiers in Physics, 2022)
Objective: We introduce a new treatment verification technique to estimate the primary particle’s stopping power from prompt gamma timing measurements in proton therapy. Approach: The starting point is the Spatio-temporal Emission Recostruction technique, which provides the time-depth distribution of the emitted prompt photons with a multiple Prompt-Gamma Timing detector setup based on Lanthanum Bromide crystals. A dedicated formalism based on an analytical approximation of the stopping power is developed to obtain the desired information. Its performance is evaluated in a proof of concept configuration via Monte Carlo simulations of monochromatic proton beams impinging on a homogeneous PMMA phantom. Main Results: Results indicate stopping power estimations as good as 3.8% with respect to NIST values, and range estimations within 0.3 cm (standard deviation), when considering 250 ps FWHM timing resolution. Significance: The current study shows, for the first time, the feasibility of evaluating the stopping power of primary beams with a technique that can be performed in-vivo, opening up new possibilities in the field of treatment verification and therapy optimization.